Washback of Microteaching Test on EFL Students’ Overseas Teaching Practice - Fitrie Amaelia; Entika Fani Prastikawati (Ahmad Dahlan Journal of English Studies, 2021)
This research aim was to investigate the washback of microteaching test on EFL students’ overseas teaching practice by presenting two main data on the influence of microteaching test on EFL students’ overseas teaching practice, and the contribution of microteaching test on EFL students’ overseas teaching practice. This research applied descriptive qualitative research design by distributing a questionnaire and followed by a semi-structured interview. The subjects of the research were ten EFL students who had contributed to overseas teaching practice. The research revealed two main results. The result showed that most of the respondents (80%) agreed that the microteaching test had a significant influence on their teaching practice in terms of teaching and learning process, their teaching skills, their confidence, and reduced anxiety and fear. Further, the microteaching test was revealed for having a crucial contribution to their teaching practice. It also was supported by the detailed finding that those contributions were managing a classroom, selecting teaching goals and lesson plans, increasing the speaking ability, delivering the teaching materials, and managing time effectively.